Faktor Risiko yang Mempengaruhi Kejadian Malaria Di Indonesia : Review Literatur 2016-2020 - Maurend Yayank Lewinsca; Mursid Raharjo; Nurjazuli Nurjazuli (POLTEKKES KEMENKES MANADO, 2021)
Malaria is a disease that is still a world health problem, in 2019 the number of malaria cases reached 229 million people. Indonesia is a developing region with a tropical and subtropical climate that is favored by Anopheles sp. Mosquitoes as their habitat. Malaria cases in Indonesia have increased based on the indicator of Annual Parasite Incidence (API) malaria and outbreaks (KLB) in several endemic areas. The purpose of this study was to determine the factors that influence the incidence of malaria in Indonesia by using literature studies in the last 5 years (2016-2020). The method used was a literature review with a literature search component, inclusion exclusion criteria, and study selection and quality assessment. The number of samples of this study were 22 samples of research articles. The results showed that there are several factors that most dominate the incidence of malaria in Indonesia, namely the use of mosquito nets (11 articles), the presence of breeding places (9 articles), the habit of going out at night (9 articles), and the use of mosquito repellents (5 articles). It is hoped that people in malaria endemic areas can use mosquito nets at night, always clean standing water around the house, avoid outdoor activities at night if not needed, and can avoid mosquito bites by using mosquito repellent.